Cultural Heritage Protection as a Security Issue in the 21st Century: Recent Developments - von Schorlemer, Sabine (Indonesian Journal of International Law, 2018)
Throughout history, cultural property has permanently been at risk in armed conflict as belligerents always aimed at razing to the ground or plundering the enemy’s cultural heritage. Cultural property is a war victim time and again, either by armed attack or by collateral damage. This background opens the way for new insights into research on cultural heritage protection as a security issue in the 21st century. In order to fight the root causes of heritage destruction and extremism, UNESCO is advocating strongly a comprehensive approach, using also its “soft power” across the Organization’s mandate. Thus, despite its limited resources, UNESCO is an important actor in promoting a culture of peace, justice and tolerance on a worldwide scale.